حل المجلس الشعبي الوطني - غدير, احمد بدر الدين (جامعة الوادي university el-oued, 2022)
We devoted the chapter of our research to studying the conceptual framework of the mechanism of dissolving the National People's Assembly, as we highlighted the various definitions to give them to the mechanism of the solution. A king, a prince, or a president of a republic. But if the solution takes place at the request of the ministry in the event of a dispute between it and Parliament, we will be before the image of the ministerial solution, and the solution may be by force of law in certain cases specified by the constitution. What is termed as self-dissolution, and as the popular will can be the source of the solution, it is issued by direct popular will, which is known as the popular solution. Chapter Summary In this chapter, we dealt with in the first topic the constitutional procedures that precede the dissolution of the People’s National Assembly, which is a set of procedures carried out by the President of the Republic. Consultation before dissolving the People’s National Assembly, and this is what we discussed in the first section, then holding prior legislative elections, which we discussed in the second section, then finally the self-dissolution of the National People’s Assembly, and this is what we discussed in the third section. Constitutionally empowered to dissolve the People’s National Assembly, so we divided it into two branches: In the first section, we dealt with the authority authorized to issue a decree dissolving the People’s National Assembly, which is the President of the Republic, as he is the protector of the constitution, based on Article 147 of the 2016 Constitution. Signing In the second topic, we discussed the legal consequences resulting from the mechanism of dissolving the National People's Assembly, as it is from the stage of completing the procedure. A, which is represented in the set of results that fall on the legislative and executive bodies. As for those related to the legislative institution, it is represented in the disruption and inertia of the function of the National Assembly, as well as the application of the theory represented in the loss of members of the National People’s Assembly and their parliamentary custody. As for the executive body, the effects of the incident are manifested in the resignation The government and the appointment of a new staff by the President of the Republic, as well as granting the President of the Republic the authority to legislate by orders, until the election of a new People’s Assembly. Secondly, the effects of the solution on the performance of the National Assembly, then thirdly, the legal situation presented to Parliament for a vote before its dissolution. Then we touched in the second demand on the effects of the solution on the executive authority, which includes the following branches: First, the effects of the solution on the work of the government, Secondly, the effects of the solution on the powers and competencies of the President of the Republic
مذكرة ماستر
Keywords: : National People'sAssembly, politics, parliament, executiveauthority